Comparative Analysis of Text Mining Results With Tf ldf Features and SQL Like Operator in Indonesian News Search - Riwa Rambu Hada Enda; Fajar Hariadi (Universitas Muhammadiyah Sidoarjo, 2020)
Research on the implementation of text mining uses the TF IDF method to be used in the Information retrieval / Indonesian news search feature. The dataset used was sourced from NewsAPI and built a Codeigniter based website named